Tanggapan Pemuda Kristen terhadap Penalaran Kitab Suci Lintas Agama: Sebuah Analisis Deskriptif dari Perspektif Keramahtamahan - Nelwan, Gerry (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
The reading of Scripture is susceptible to interpretation and can offer constructive values, but it can also lead to self-exclusion and destructive actions. Traditionally, the reading and interpretation of Scripture have been an internal activity within each religious community. However, in Yogyakarta, Scriptural Reasoning activities are being organized by the Young Interfaith Peacemaker Community (YIPC) Indonesia, involving participants from diverse religious and belief backgrounds. This research examines the response of Christian Youth engaged in Scriptural Reasoning activities, specifically focusing on how they create a welcoming space for the presence of the other. The research will employ an analytical descriptive method, with data gathered through participatory observation, interviews with respondents selected via purposive sampling, and the collection of relevant literature and documents. Respondents will include organizers of Scriptural Reasoning activities and Christian participants. The data will be analyzed using Marianne Moyaert’s concept of hermeneutic hospitality. This study highlights the significance of hermeneutic openness as an expression of hospitality within the Christian community and the importance of creating space for interreligious dialogue. Reading sacred texts can also help prevent conflicts of religious sentiments based on scriptural interpretation.